Time to Say Goodbye to Bronchiolitis, Viral Wheeze, Reactive Airways Disease, Wheeze Bronchitis and All That - Douros, Konstantinos; Everard, Mark L. (Frontiers in Pediatrics, 2020)
The diagnosis and management of infants and children with a significant viral lower respiratory tract illness remains the subject of much debate and little progress. Over the decades various terms for such illnesses have been in and fallen out of fashion or have evolved to mean different things to different clinicians. Terms such as ‘bronchiolitis’, ‘reactive airways disease’, ‘viral wheeze’ and many more are used to describe the same condition and the same term is frequently used to describe illnesses caused by completely different dominant pathologies. This lack of clarity is due, in large part, to a failure to understand the basic underlying inflammatory and associated processes and, in part, due to the lack of a simple test to identify a condition such as asthma. Moreover, there is a lack of insight into the fact that the same pathology can produce different clinical signs at different ages. The consequence is that terminology and fashions in treatment have tended to go around in circles. As was noted almost 60 years ago, amongst pre-school children with a viral LRTI and airways obstruction there are those with a ‘viral bronchitis’ and those with asthma. In the former group, a neutrophil dominated inflammation response is responsible for the airways obstruction whilst amongst asthmatics much of the obstruction is attributable to bronchoconstriction. The airways obstruction in the former group is predominantly caused by airways secretions and to some extent mucosal oedema (a ‘snotty lung’). These patients benefit from good supportive care including supplemental oxygen if required (though those with a pre-existing bacterial bronchitis will also benefit from antibiotics). For those with a viral exacerbation of asthma, characterised by bronchoconstriction combined with impaired -agonist responsiveness, standard management of an exacerbation of asthma (including the use of steroids to re-establish bronchodilator responsiveness) represents optimal treatment. The difficulty is identifying which group a particular patient falls into. A proposed simplified approach to the nomenclature used to categorise virus associated LRTIs is presented based on an understanding of the underlying pathological processes and how these contribute to the physical signs.